2015
DOI: 10.18632/oncotarget.5517
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular characterization of cancer stem-like cells in bladder cancer: a potential signature for muscle-invasive tumors

Abstract: Striking evidence associates cancer stem cells (CSCs) to the high recurrence rates and poor survival of patients with muscle-invasive bladder cancer (BC). However, the prognostic implication of those cells in risk stratification is not firmly established, mainly due to the functional and phenotypic heterogeneity of CSCs populations, as well as, to the conflicting data regarding their identification based on a single specific marker. This emphasizes the need to exploit putative CSC-related molecular markers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…We observed that expression of ARRB2 inversely correlated with CSC properties such as expression of CSC markers and selfrenewal potential in bladder cancer cell lines. A recent study demonstrated that ALDH2 and SOX2 provide a 2-gene stem-like signature that discriminates muscle-invasive from nonmuscle invasive tumors with an accuracy of 93% (43). Interestingly, we did not observe any significant effect on expression of SOX2 upon overexpression of ARRB2 in HT1376 and 5637 cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 54%
“…We observed that expression of ARRB2 inversely correlated with CSC properties such as expression of CSC markers and selfrenewal potential in bladder cancer cell lines. A recent study demonstrated that ALDH2 and SOX2 provide a 2-gene stem-like signature that discriminates muscle-invasive from nonmuscle invasive tumors with an accuracy of 93% (43). Interestingly, we did not observe any significant effect on expression of SOX2 upon overexpression of ARRB2 in HT1376 and 5637 cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 54%
“…We tested whether NK cells could induce CSCs towards a more differentiated phenotype rendering them susceptible to chemotherapy. Therefore, spheres were incubated with the supernatants of activated-NK cells for 4 h, followed by analysis of stemness related markers previously identified [5]. The ALDH activity, considered a functional readout of stemness, decreased by 60 % in spheres after 4 h incubation with NK supernatants (Fig.…”
Section: Supernatants From Nk Cells Induce Differentiation and Sensitmentioning
confidence: 87%
“…Cultured cells were then stained with fluorochromeconjugated monoclonal antibodies against human blood surface antigens: CD3 PerCP/Cy5. 5 After a 4-h incubation period, the supernatants were harvested and counted for released radioactivity in a gamma counter (CRC-55tW Capintec), within a 51 Cr sensitivity energy window (300-400 keV). The specific lysis of target cells was calculated as follows: Percentage of specific lysis = (experimental release -spontaneous release)/(maximum release -spontaneous release) × 100.…”
Section: Cd107a Degranulation and Cytokine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder cancer (BCa) is one of the most common malignancies, with high recurrence rate . As we all know, cancer stem cells (CSCs) may play an important role in tumor growth . Eliminating CSCs is a key issue in eradicating tumor.…”
mentioning
confidence: 99%